Activation of the high-affinity immunoglobulin E receptor Fc epsilon RI in RBL-2H3 cells is inhibited by Syk SH2 domains. - Taylor, J A (1995)
Antigen-mediated aggregation of the high-affinity receptor for immunoglobulin E, Fc epsilon RI, results in the activation of multiple signaling pathways, leading to the release of mediators of the allergic response. One of the earliest responses to receptor stimulation is the tyrosine phosphorylation of the beta and gamma subunits of Fc epsilon RI and the association of the tyrosine kinase Syk with the phosphorylated receptor. This association is mediated by the SH2 domains of Syk and is believed to be critical for activating signaling pathways resulting in mediator release. To examine the importance of the interaction of Syk with Fc epsilon RI in signaling events following receptor activation, we introduced a protein containing the SH2 domains of Syk into streptolysin O-permeabilized RBL-2H3 cells. The Syk SH2 domains completely inhibited degranulation and leukotriene production following receptor aggregation, and they blocked the increase in protein tyrosine phosphorylation observed after receptor activation. Inhibition was specific for Fc epsilon RI-mediated signaling, since degranulation of cells activated by alternative stimuli was not blocked by the Syk SH2 domains. A protein containing a point mutation in the carboxy-terminal SH2 domain which abolishes phosphotyrosine binding was not inhibitory. In addition, inhibition of degranulation was reversed by pretreatment of the SH2 domains with a tyrosine phosphorylated peptide corresponding to the tyrosine-based activation motif found in the gamma subunit of Fc epsilon RI, the nonphosphorylated peptide had no effect. The association of Syk with the tyrosine-phosphorylated gamma subunit of the activated receptor was blocked by the Syk SH2 domains, and deregulation in cells activated by clustering of Syk directly without Fc epsilon RI aggregation was not affected by the Syk SH2 domains. These results demonstrate that the association of Syk with the activated Fc epsilon RI is critical for both early and late events following receptor activation and confirm the key role Syk plays in signaling through the high-affinity IgE receptor.